Higher Education and the Challenges for Economic Growth in Mozambique: Some Evidence - Uetela, Pedro [UNESP] (Hipatia Press, 2015)
There has been an increasing debate on higher education ( HE) transformation in developing countries over the past decades. The main assumption underlying this focus often centers on the arguments contrary to the dominant narratives, which have been skeptical that HE plays a considerable role for economic and social transformation. The rise of certain Asian economies including Taiwan and South Korea, which were at the same level in terms of GDP with African nation states such as Nigeria, Tanzania and Ghana in the 1960s, has confirmed the theory that maximization of knowledge is key to achieve development. Furthermore, the successful stories from the newly industrialized countries especially the BRICS have considerably increased the possibilities that Mozambique can learn from borrowed and contextualized policies from those states. In this article I highlight the main changes that have recently shaped HE policy and governance including today challenges it faces. In so doing, I outline recommendations for both policy makers and higher education leaders on how they can make appropriation of the experiences that have worked in the global context to ensure the creation of local workforce capable of driving both economic and social development in the country based on knowledge investment.
Keywords: higher education; Mozambique; knowledge economy; development